Fourier-space combination of Planck and Herschel images - Abreu Vicente, Jorge; Ballesteros-Paredes, Javier (Astronomy and astrophysics, 2017)
Context. Herschel has revolutionized our ability to measure column densities (NH) and temperatures (T) of molecular clouds thanks to its far infrared multiwavelength coverage. However, the lack of a well defined background intensity level in the Herschel data limits the accuracy of the NH and T maps. Aims. We aim to provide a method that corrects the missing Herschel background intensity levels using the Planck model for foreground Galactic thermal dust emission. For the Herschel/PACS data, both the constant-offset as well as the spatial dependence of the missing background must be addressed. For the Herschel/SPIRE data, the constant-offset correction has already been applied to the archival data so we are primarily concerned with the spatial dependence, which is most important at 250 μm.Methods. We present a Fourier method that combines the publicly available Planck model on large angular scales with the Herschel images on smaller angular scales.Results. We have applied our method to two regions spanning a range of Galactic environments: Perseus and the Galactic plane region around l = 11deg (HiGal-11). We post-processed the combined dust continuum emission images to generate column density and temperature maps. We compared these to previously adopted constant-offset corrections. We find significant differences (≳20%) over significant (~15%) areas of the maps, at low column densities (NH ≲ 1022 cm-2) and relatively high temperatures (T ≳ 20 K). We have also applied our method to synthetic observations of a simulated molecular cloud to validate our method.Conclusions. Our method successfully corrects the Herschel images, including both the constant-offset intensity level and the scale-dependent background variations measured by Planck. Our method improves the previous constant-offset corrections, which did not account for variations in the background emission levels.
Gesehen am 26.09.2018